1988
DOI: 10.1080/00071668808417111
|View full text |Cite
|
Sign up to set email alerts
|

Age and strain differences in plumage renewal during natural and induced moulting in hybrid hens

Abstract: 1. Replacement of remiges and body-feathers was studied in several flocks of brown and white layers and broiler-breeders under near commercial conditions. 2. Spontaneous moulting of primaries was not circannual in modern laying hybrids; moulting response was more retarded in brown than in white hens. 3. Following induction of moulting by a standard procedure in brown hens, the extent of replacement of remiges increased with increasing age, but even at 81 weeks of age, moult was not completed, but ceased when h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1988
1988
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The delayed onset of egg production in the 25% body weight loss hens agrees with the findings of Herremans (1988), who reported that their greater body weight loss hens (30%) had extended cessation of egg-laying but had the best laying performance once production was resumed. Hens with the greatest body weight loss would have been delayed in physiological recovery for reproduction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The delayed onset of egg production in the 25% body weight loss hens agrees with the findings of Herremans (1988), who reported that their greater body weight loss hens (30%) had extended cessation of egg-laying but had the best laying performance once production was resumed. Hens with the greatest body weight loss would have been delayed in physiological recovery for reproduction.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it is emphasized that there have been several reports of hen's age, body weight at the initiation and during the molt, environmental temperature, and strain interactions between postmolt egg performance and molt induction procedures (Baker et ah, 1983;Cunningham and McCormick, 1985;Herremans, 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Several researchers (Herremans, 1988;Gonzalez, 1988;Brake, 1993) reported that decreased body weight during molting period might have a relation with restricted feeding. Ruszler (1998) showed that for successful molting the body weight loss should be between 15-40% during molting period.…”
Section: Body Weight Changementioning
confidence: 99%
“…Hens in battery-cages are gradually subject to cumulative feather wear and this results in decreased laying efficiency (Hurnik et al, 1977;Leeson and Morrison, 1978). Various methods of inducing moulting can result in different extents of plumage renewal Herremans, 1988). Following induced moulting, energy requirements are decreased to values comparable to those of pullets (Tauson and Svensson, 1980).…”
Section: Introductionmentioning
confidence: 98%